Hegel in the Americas: Interpretive Assimilation and the Anticolonial Argument (Revista Eletrônica Estudos Hegelianos, 2019)
This essay criticizes some strategies of Hegel scholarship, especially the non-metaphysical school and its recent metaphysical successor. My main claim is that these approaches are rhetorically opaque, and thus vulnerable to a certain anticolonial argument. In place of these strategies, I recommend and illustrate a more historically perspicuous approach that is sensitive to concerns about the role of European philosophy in the Americas.